Invaders Toast Chaconia Gold - Joseph, Terry (Express)
The Petrotrin Invaders Steel Orchestra celebrated as they were awarded a Chaconia Gold Medal. A function was held to celebrate their national award and it turned into to forum for the band's pioneers to share some history with the current players. Vernon "Birdie" Mannette, Francis Wickham and Norman Darway spoke about the journey of the steelband.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago -- History; Steel band music -- Trinidad and Tobago